Fra resultatkontrakt til mål- og resultatplan: Ny inspiration til realiseringen af resultatstyringens potentialer - Brødsgaard, Marie-Louise Frølich; Kristiansen, Mads Bøge (Politik, 2015)
Since the introduction of performance contracts in central government, the Ministry of Finance has regularly launched new publications containing recommendations for the design and implementation of management by objectives and results. In the fall 2014 the Ministry of Finance presented a new model for management by objectives and results in central government. is article presents an interview with central actors involved in development of the new model. e interview focuses on the background for the revisions of the existing concept for management by objectives and results, the contents of the new model, and why the new model is expected to be able to solve the challenges, the existing concept is said to be characterized by. In the new model, the Ministry of Finance recommends that steering documents should contain fewer targets, more precisely de ned targets as well as they should be anchored in the top management.